Involuntariness in negligence actions. (March 2023) - Bogle, Stephen
Abstract: In a negligence action against a defendant suffering from a mental disorder or an incapacity, a key but neglected question is what we mean by involuntariness. Although involuntariness is an accepted response, its relationship to mental or physical incapacity is poorly understood. The existing authorities offer only basic instruction about what is meant by involuntariness. Moreover, there is a suspicion that involuntariness undermines the objectivity of the standard of care. However, in this paper, it is argued that involuntariness can be better defined and a clearer understanding can be gained of how responsibility operates within tort law. By relating the case law and commentary on involuntariness to a choice theory of responsibility and arguing that this operates at a foundational level which is analytically prior to questions of breach, this paper tries to illuminate how tort law – like other areas of law – makes fundamental assumptions about the capacity of individuals to whom duties are expected to apply. None of this will necessarily increase the volume of claims or unsettle well-worn authorities but it does ensure both consistency and fairness and argues for a deeper appreciation of agency within how tort law characterises the applicability of duties.